Taxonomical and Phytochemical Characterization of Two Highly Traded Medicinal Species of Genus Berberis: Taxonomical and Phytochemical Characterization of two Medicinal Species of Genus Berberis - Ahmed, Sidra Nisar; Ahmad, Mushtaq; Zafar, Muhammad; Rashid, Sofia; Yaseen, Ghulam; Ashfaq, Shomaila; Sultana, Shazia (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
TThe medicinal plants serve as an important natural source and potentially safe medicinal drugs that can play a significant role in moderating human health by contributing towards herbal medicines. The genus Berberis exhibits evergreen and deciduous shrubs like Berberis aristata DC and Berberis lyceum Royal. These medicinal plants are used as a remedy for swollen and sore eyes, skin diseases, healing of broken bones, curative piles, jaundice and diarrhea. The morphological and organoleptic studies concluded that fruit of Berberis aristata encloses two seeds while Berberis lyceum encloses three seeds. The total flavonoid content (134.33mg GAE/g) and phenolic content (39.23 mg QE/g) in Berberis aristata is high as compared to flavonoid content (115.01 mg GAE/g) and phenolic content (33.03 mg QE/g) of Berberis lyceum. The results achieved provide us with valuable information for botanical quality control and species identification and assist us to detect adulterations in commercial as well as in laboratory samples.